Propuesta para el Control de Costos en la empresa constructora KVA Ingeniería de Centroamérica S.A. - Nuñez-Guerrero, Oscar Alberto (Instituto Tecnológico de Costa Rica., 2016)
According to the problems found in the Enterprise KVA Ingeniería de Centroamérica S.A. in terms of control of costs, it has been done a practice. This practice will allow to identify weaknesses in the company and find solutions by giving some proposals. Then, to develop this document it was necessary to study the current situation in the Company that is why, the procedures followed when developing the control of costs were studied. After this, weaknesses were discovered and this project gave some possible solutions. Finally, there was a tool that made easy and fast the process of the control of costs. It made integral this process and the one for controlling costs.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Materiales; Mano de Obra; Supervisión; Presupuesto; Inventario